Compound and preparation method thereof, flame retardant, flexibilizer, material modifier, high polymer material and preparation method thereof, and packaging product
By preparing compounds containing phosphate ester structures, nitrogen-containing heterocyclic structures, and hydroxyl groups, the problems of insufficient mechanical properties and flame retardancy in materials such as polylactic acid have been solved, and the flame retardant and mechanical properties of the materials have been significantly improved.
Patent Information
- Application Number
- CN202510986999.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-17
- Publication Date
- 2025-11-11
AI Technical Summary
Existing biodegradable polymer materials such as polylactic acid have shortcomings in terms of mechanical properties and flame retardancy, which limits their large-scale application in high-end fields.
By preparing a compound containing a phosphate ester structure, a nitrogen-containing heterocyclic structure, and hydroxyl groups, the compound is constructed using a four-step reaction to improve the flame retardant and mechanical properties of the material.
The compound significantly improves the flame retardant and mechanical properties of the material through a dual flame retardant mechanism involving both the gas phase and condensed phase, thereby achieving a comprehensive performance enhancement.
Smart Images

Figure SMS_2 
Figure SMS_4 
Figure SMS_5
Abstract
Description
Technical Field
[0001] This application belongs to the field of materials, specifically relating to a compound and its preparation method, flame retardants, toughening agents, material modifiers, polymer materials and their preparation methods, and packaging products. Background Technology
[0002] With the continuous development of materials science, polymer materials have been widely used in many fields such as electronics, automobile manufacturing, biomedicine, and packaging materials due to their lightweight, high strength, and ease of processing. Among them, biodegradable polymer materials such as polylactic acid (PLA) have become a research hotspot due to their excellent biodegradability.
[0003] However, existing biodegradable polymer materials such as polylactic acid have shortcomings in terms of mechanical properties and flame retardancy, which seriously restrict their large-scale application in high-end fields. Summary of the Invention
[0004] This application aims to at least partially solve one of the technical problems in related technologies. Therefore, the purpose of this application is to provide a compound and its preparation method, a flame retardant, a toughening agent, a material modifier, a polymer material and its preparation method, and packaging articles. The compound provided in this application contains phosphate ester structures, nitrogen-containing heterocyclic structures, and hydroxyl groups, endowing it with excellent flame retardancy, reactivity, and energy dissipation capabilities, among other multifunctional properties. Therefore, when this compound is applied to the modification of materials such as polylactic acid, it can significantly improve the flame retardant and mechanical properties of the materials, and has a wide range of applications.
[0005] This application firstly discloses a compound. According to embodiments of this application, the general chemical structural formula of the compound is shown in Formula I;
[0006] Equation I: R is a substituent containing a hydroxyl group.
[0007] The compounds described in the above embodiments of this application contain phosphate ester structures, nitrogen-containing heterocyclic structures, and hydroxyl groups, which endow them with multiple functional properties such as excellent flame retardancy, reactivity, and energy dissipation capacity. Therefore, when these compounds are used to modify materials such as polylactic acid, they can significantly improve the flame retardant and mechanical properties of the materials, making them widely applicable.
[0008] In addition, the compounds according to the above embodiments of this application may also have the following additional technical features:
[0009] In some embodiments of this application, R is selected from any of the following substituents:
[0010]
[0011] In some embodiments of this application, the chemical structural formula of the compound is shown in Formula II;
[0012] Formula II:
[0013] A second aspect of this application provides a method for preparing the compound described in any one of the first aspects. According to embodiments of this application, the method for preparing the compound includes the following steps:
[0014] 4-hydroxybenzaldehyde and a phosphorylating agent were reacted in the first reaction to give intermediate A;
[0015] A second reaction is carried out with paraformaldehyde, ethylenediamine and eugenol to obtain intermediate B;
[0016] Intermediate A and intermediate B are subjected to a third reaction to obtain intermediate C;
[0017] The intermediate C and a thiol-containing alcohol compound are subjected to a fourth reaction to obtain the compound;
[0018] The chemical structural formula of intermediate A is shown below:
[0019]
[0020] The chemical structural formula of intermediate B is shown below:
[0021]
[0022] The chemical structural formula of intermediate C is shown below:
[0023]
[0024] The preparation method of the compounds described in the above embodiments of this application successfully constructs chemical structures such as phosphate ester structures, nitrogen-containing heterocyclic structures, and hydroxyl groups in the compounds through a four-step reaction, endowing them with multiple functional properties such as excellent flame retardancy, reactivity, and energy dissipation capacity.
[0025] In addition, the preparation method of the compound according to the above embodiments of this application may also have the following additional technical features:
[0026] In some embodiments of this application, the step of reacting 4-hydroxybenzaldehyde with a phosphorylating agent to obtain intermediate A includes the following process:
[0027] Under the protection of an inert atmosphere and the action of an alkaline catalyst, the 4-hydroxybenzaldehyde and the phosphorylating agent are subjected to the first reaction at a temperature of 20-30°C for 2-3 hours to obtain the intermediate A;
[0028] The weight ratio of the 4-hydroxybenzaldehyde, the phosphorylating agent, and the alkaline catalyst is (10-12):(18-22):(13-15), the alkaline catalyst includes at least one of triethylamine, pyridine, and diisopropylethylamine, and the phosphorylating agent includes at least one of phosphorus oxychloride and phosphorus oxybromide.
[0029] And / or, the step of subjecting paraformaldehyde, ethylenediamine, and eugenol to a second reaction to obtain intermediate B includes the following processes:
[0030] The paraformaldehyde and the ethylenediamine are mixed to obtain a premixed system;
[0031] Add the eugenol dropwise to the premixed system and heat to 80-90°C. After the addition is complete, heat to 110-120°C to carry out the second reaction for 3-4 hours to obtain intermediate B.
[0032] The weight ratio of the paraformaldehyde, the ethylenediamine and the eugenol is (10-12):(11-13):(30-35);
[0033] And / or, the step of subjecting intermediate A and intermediate B to a third reaction to obtain intermediate C includes the following process:
[0034] Under the action of an acidic catalyst, intermediate A and intermediate B are subjected to the third reaction at a temperature of 40-50°C for 3-4 hours to obtain intermediate C;
[0035] The weight ratio of intermediate A, intermediate B and acidic catalyst is (10-12):(12-15):(1-2), and the acidic catalyst includes at least one of acetic acid and p-toluenesulfonic acid.
[0036] And / or, the step of subjecting the intermediate C and a thiol-containing alcohol compound to a fourth reaction to obtain the compound includes the following process:
[0037] Under light irradiation and with the aid of a photoinitiator, the intermediate C and the thiol-containing alcohol compound were subjected to the fourth reaction at a temperature of 20–30°C for 2–4 hours to obtain the compound.
[0038] The intermediate C, the mercapto-containing alcohol compound, and the photoinitiator are in a weight ratio of (10-12):(8-10):(1-2). The photoinitiator includes at least one of 2,2-dimethoxy-2-phenylacetophenone and 2-hydroxy-2-methyl-1-phenyl-1-propanone. The mercapto-containing alcohol compound includes at least one of 3-mercapto-1,2-propanediol and 3-mercapto-1-propanol.
[0039] A third aspect of this application provides a flame retardant. According to embodiments of this application, the flame retardant comprises a compound as described in any one of the first aspects or a compound prepared using the method described in any one of the second aspects.
[0040] The flame retardant described in the above embodiments of this application comprises the compound described in any one of the first aspects or a compound prepared by the method described in any one of the second aspects. Therefore, the flame retardant possesses multiple functional properties such as excellent flame retardancy, reactivity, and energy dissipation capacity.
[0041] A fourth aspect of this application discloses a toughening agent. According to embodiments of this application, the toughening agent comprises the compound described in any one of the first aspects or a compound prepared using the method described in any one of the second aspects.
[0042] The toughening agent described in the above embodiments of this application comprises the compound described in any one of the first aspects or a compound prepared by the method described in any one of the second aspects. Therefore, the toughening agent possesses multiple functional properties such as excellent flame retardancy, reactivity, and energy dissipation capability.
[0043] A fifth aspect of this application discloses a material modifier. According to embodiments of this application, the material modifier comprises a compound as described in any one of the first aspects or a compound prepared using the method described in any one of the second aspects.
[0044] The material modifier described in the above embodiments of this application comprises a compound as described in any one of the first aspects or a compound prepared using the method described in any one of the second aspects. Therefore, the material modifier possesses multiple functional properties such as excellent flame retardancy, reactivity, and energy dissipation capability.
[0045] A sixth aspect of this application discloses a polymer material. According to embodiments of this application, the raw materials for the polymer material include the compounds described in any one of the first aspects or compounds prepared using the preparation method of the compounds described in any one of the second aspects.
[0046] The polymer material described in the above embodiments of this application is modified by introducing the compound described in any one of the first aspects or by using the preparation method of the compound described in any one of the second aspects. As a result, the overall properties of the polymer material, such as flame retardant properties and mechanical properties, are significantly improved.
[0047] In addition, the polymer material according to the above embodiments of this application may also have the following additional technical features:
[0048] In some embodiments of this application, the polymeric material comprises the following raw materials in parts by weight:
[0049] 70-80 parts of a polylactic acid compound containing a carboxyl group and 3-4 parts of the compound.
[0050] In some embodiments of this application, the polymer material further includes the following raw materials in parts by weight:
[0051] 20-22 parts of cellulose compounds;
[0052] And / or, by weight, the polymeric material further includes the following raw materials:
[0053] 20-22 parts of cellulose compounds, 8-10 parts of plasticizer, 1-2 parts of lubricant, and 0.1-0.2 parts of esterification catalyst;
[0054] And / or, by weight, the polymeric material further includes the following raw materials:
[0055] The mixture contains 20-22 parts of cellulose compounds, 8-10 parts of plasticizer, 1-2 parts of lubricant, 0.1-0.2 parts of esterification catalyst, and 3-4 parts of filler.
[0056] In some embodiments of this application, the cellulose compound includes at least one of cellulose acetate, carboxymethyl cellulose, and hydroxyethyl cellulose;
[0057] And / or, the plasticizer includes at least one of polyethylene glycol, triacetin, and citrate;
[0058] And / or, the lubricant comprises at least one of zinc stearate, calcium stearate, barium stearate, and polyethylene wax;
[0059] And / or, the filler comprises at least one of layered silicate and nano silica;
[0060] And / or, the esterification catalyst includes at least one of zinc acetate and zinc propionate.
[0061] In some embodiments of this application, the biodegradability of the polymer material is 82.7–88.9%.
[0062] In some embodiments of this application, the tensile strength of the polymer material is 54.2 to 60.5 MPa.
[0063] In some embodiments of this application, the limiting oxygen index of the polymeric material is 30.2 to 33.4%.
[0064] A seventh aspect of this application provides a method for preparing a polymeric material as described in any one of the sixth aspects above. According to an embodiment of this application, the method for preparing the polymeric material includes the following steps:
[0065] The raw material components of a polymer material are mixed to obtain a mixture;
[0066] The mixture is melt-blended and extruded to obtain the polymer material.
[0067] The present application describes a method for preparing polymeric materials according to the above embodiments. This method introduces the aforementioned compounds through melt blending and extrusion molding to modify the material. Consequently, the overall properties of the polymeric material, including its flame retardant and mechanical properties, are significantly improved.
[0068] In addition, the preparation method of the polymer material according to the above embodiments of this application may also have the following additional technical features:
[0069] In some embodiments of this application, the equipment for melt blending and extrusion molding of the mixture includes a twin-screw extruder. The operating parameters of the twin-screw extruder include: conveying section temperature of 150-160°C, melting section temperature of 170-180°C, mixing section temperature of 180-190°C, homogenization section temperature of 175-185°C, and die head temperature of 170-180°C.
[0070] An eighth aspect of this application discloses a packaging article. According to an embodiment of this application, the raw materials of the packaging article include the compound described in any one of the first aspects, the compound prepared by the method described in any one of the second aspects, the polymer material described in any one of the sixth aspects, or the polymer material prepared by the method described in any one of the seventh aspects.
[0071] The packaging articles described in the above embodiments of this application are made from the aforementioned compounds or polymeric materials. Therefore, these packaging articles possess excellent flame-retardant properties and mechanical properties.
[0072] In addition, the packaging articles according to the above embodiments of this application may also have the following additional technical features:
[0073] In some embodiments of this application, the packaging articles include at least one of coffee cup lids, milk tea cups, packaging bags, lunch boxes, and headphone cases.
[0074] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of this application. Detailed Implementation
[0075] The embodiments of this application are described in detail below by way of example, and are intended to explain this application, but should not be construed as limiting this application.
[0076] This application firstly discloses a compound. According to embodiments of this application, the general chemical structural formula of the compound is shown in Formula I;
[0077] Equation I: R is a substituent containing a hydroxyl group.
[0078] Currently, existing biodegradable polymer materials have shortcomings in terms of mechanical properties and flame retardancy, which severely restricts their large-scale application in high-end fields. Taking polylactic acid (PLA) as an example, existing technologies mainly suffer from the following key defects:
[0079] 1) A prominent contradiction exists between mechanical properties and biodegradability: Traditional polylactic acid (PLA) materials lack sufficient toughness and strength, making it difficult to meet the requirements of engineering applications. Although existing toughening modification technologies (such as adding elastomers or inorganic fillers) can improve mechanical properties, they generally come at the cost of sacrificing the biodegradability of PLA, making it difficult for materials to balance environmental friendliness and functional durability.
[0080] 2) Significant conflict between flame retardant modification and degradation performance: PLA has a limiting oxygen index (LOI) of only about 19%, making it a flammable material. While conventional flame retardants (such as halogenated and phosphorus-based compounds) can improve flame retardancy, they significantly reduce the degradation rate of the material. Moreover, most flame retardants have poor compatibility with the PLA matrix, posing a risk of migration and precipitation, which can easily lead to performance degradation with long-term use.
[0081] 3) Poor interfacial bonding: Existing modification methods mostly rely on physical blending. The modifying components such as flame retardants are only bonded to the PLA matrix through weak interfacial interactions, making it difficult to form stable chemical bonds or nanoscale dispersion structures. This heterogeneous system makes the material prone to phase separation during thermal processing or use, and it is impossible to achieve synergistic optimization of mechanical properties, flame retardancy, and biodegradability.
[0082] The compounds described in the above embodiments of this application contain a phosphate ester structure (which can be represented as O=P(OR)3, where R is a substituent), a nitrogen-containing heterocyclic structure, and hydroxyl groups (-OH), endowing them with excellent flame retardancy, reactivity, and energy dissipation capabilities, among other multifunctional properties. Therefore, when applied to the modification of materials such as polylactic acid, these compounds can significantly improve the flame retardant and mechanical properties of the materials, making them widely applicable. Specifically:
[0083] 1) The phosphate ester structure in this compound decomposes at high temperatures to generate phosphoric acid substances. These substances can catalyze the dehydration of polymers such as polylactic acid (PLA) to form char, creating a dense char layer that isolates heat and oxygen. Furthermore, the PO· free radicals generated from the decomposition of these substances can capture H· and HO· active free radicals in the combustion chain reaction, effectively inhibiting the gas-phase combustion reaction. Simultaneously, the nitrogen-containing heterocycles in the compound undergo ring-opening reactions upon heating, which enhances the thermal stability of materials such as PLA and further promotes char layer formation, strengthening the thermal barrier effect. Moreover, the nitrogen gas generated from the decomposition of the nitrogen-containing heterocycles can dilute combustible gases, while the char layer acts as a physical barrier to delay heat transfer. Therefore, the compound provided in this application achieves highly efficient flame retardancy through a dual mechanism of gas-phase flame retardancy (interrupting the combustion chain reaction by releasing gaseous free radical scavengers) and condensed-phase flame retardancy (isolieving heat and oxygen through char formation or barriers). These two mechanisms work synergistically to achieve this effect.
[0084] 2) The multiple hydroxyl groups in this compound can form a high-density hydrogen bond network with carboxyl groups (-COOH) in polymers such as polylactic acid. Under external force, energy dissipation is achieved through the dynamic breaking / reorganization of the hydrogen bond network, thereby significantly improving the toughness of the material. Furthermore, at suitable processing temperatures, some of the hydroxyl groups in this compound can undergo in-situ esterification with the carboxyl groups, forming covalently bonded chemical crosslinking points, greatly enhancing the interfacial bonding strength between the compound and the material. Simultaneously, the compound contains rigid structures such as benzene rings and nitrogen-containing heterocycles, which can form rigid-flexible block structures with flexible segments (such as long carbon chains) in materials such as polylactic acid, enhancing the stress transfer efficiency of the material.
[0085] According to some specific embodiments of this application, R is selected from any of the following substituents:
[0086]
[0087] It should be noted that in the chemical structures of the above substituents It only indicates that a chemical bond is formed or broken at that point, and is not part of a substituent.
[0088] According to some specific embodiments of this application, the chemical structural formula of the compound is shown in Formula II;
[0089] Formula II:
[0090] A second aspect of this application provides a method for preparing the compound described in any one of the first aspects. According to embodiments of this application, the method for preparing the compound includes the following steps:
[0091] 4-hydroxybenzaldehyde and a phosphorylating agent were reacted in the first reaction to give intermediate A;
[0092] A second reaction is carried out with paraformaldehyde, ethylenediamine and eugenol to obtain intermediate B;
[0093] Intermediate A and intermediate B are subjected to a third reaction to obtain intermediate C;
[0094] The intermediate C and a thiol-containing alcohol compound are subjected to a fourth reaction to obtain the compound;
[0095] The chemical structural formula of intermediate A is shown below:
[0096]
[0097] The chemical structural formula of intermediate B is shown below:
[0098]
[0099] The chemical structural formula of intermediate C is shown below:
[0100]
[0101] The preparation method of the compounds described in the above embodiments of this application, through a four-step reaction, successfully constructs chemical structures such as phosphate ester structures, nitrogen-containing heterocyclic structures, and hydroxyl groups in the compounds, endowing them with multiple functional properties such as excellent flame retardancy, reactivity, and energy dissipation capacity. Specifically:
[0102] Step 1: This application uses 4-hydroxybenzaldehyde and phosphorylating agents such as phosphorus oxychloride as raw materials to react (an organic chemical reaction in which phenolic hydroxyl groups react with phosphoric acid, phosphoric anhydride, phosphoric acid chloride, or other phosphoric acid-containing compounds to generate phenolic hydroxy phosphate esters, i.e., the first reaction), to obtain intermediate A. Taking 4-hydroxybenzaldehyde and phosphorus oxychloride as an example, the specific reaction process is as follows:
[0103]
[0104] Step 2: This application uses paraformaldehyde (paraformaldehyde depolymerizes to formaldehyde), ethylenediamine (amine component), and eugenol (phenolic component containing active hydrogen) as raw materials to carry out a Mannich condensation reaction (a Mannich reaction, an organic chemical reaction in which aldehydes containing active hydrogen, such as formaldehyde, undergo a condensation reaction with amines such as primary amines, secondary amines, or ammonia to produce Mannich bases; i.e., the second reaction) to obtain intermediate B. The specific reaction process is shown below:
[0105]
[0106] Step 3: This application uses intermediate A obtained in Step 1 and intermediate B obtained in Step 2 as raw materials to carry out an aldehyde-amine condensation reaction (an organic chemical reaction in which a compound with an aldehyde group condenses with a compound with an amino group to form a Schiff base (an imine compound), i.e., the third reaction), to obtain intermediate C. The specific reaction process is shown below:
[0107]
[0108] Step 4: This application uses intermediate C obtained in Step 3 and 3-mercapto-1,2-propanediol as starting materials to carry out a thiol-ene click reaction (a free radical addition reaction based on a thiol-containing compound and a carbon-carbon double bond-containing compound, i.e., the fourth reaction) to obtain the target product—the compound shown in Formula II. The specific reaction process is as follows:
[0109]
[0110] According to some specific embodiments of this application, the step of reacting 4-hydroxybenzaldehyde with a phosphorylating agent to obtain intermediate A includes the following process:
[0111] Under the protection of an inert atmosphere and the action of an alkaline catalyst, the 4-hydroxybenzaldehyde and the phosphorylating agent are subjected to the first reaction at a temperature of 20-30°C for 2-3 hours to obtain the intermediate A;
[0112] The weight ratio of the 4-hydroxybenzaldehyde, the phosphorylating agent, and the alkaline catalyst is (10-12):(18-22):(13-15), the alkaline catalyst includes at least one of triethylamine, pyridine, and diisopropylethylamine, and the phosphorylating agent includes at least one of phosphorus oxychloride and phosphorus oxybromide.
[0113] And / or, the step of subjecting paraformaldehyde, ethylenediamine, and eugenol to a second reaction to obtain intermediate B includes the following processes:
[0114] The paraformaldehyde and the ethylenediamine are mixed to obtain a premixed system;
[0115] Add the eugenol dropwise to the premixed system and heat to 80-90°C. After the addition is complete, heat to 110-120°C to carry out the second reaction for 3-4 hours to obtain intermediate B.
[0116] The weight ratio of the paraformaldehyde, the ethylenediamine and the eugenol is (10-12):(11-13):(30-35);
[0117] And / or, the step of subjecting intermediate A and intermediate B to a third reaction to obtain intermediate C includes the following process:
[0118] Under the action of an acidic catalyst, intermediate A and intermediate B are subjected to the third reaction at a temperature of 40-50°C for 3-4 hours to obtain intermediate C;
[0119] The weight ratio of intermediate A, intermediate B and acidic catalyst is (10-12):(12-15):(1-2), and the acidic catalyst includes at least one of acetic acid and p-toluenesulfonic acid.
[0120] And / or, the step of subjecting the intermediate C and a thiol-containing alcohol compound to a fourth reaction to obtain the compound includes the following process:
[0121] Under light irradiation and with the aid of a photoinitiator, the intermediate C and the thiol-containing alcohol compound were subjected to the fourth reaction at a temperature of 20–30°C for 2–4 hours to obtain the compound.
[0122] The intermediate C, the mercapto-containing alcohol compound, and the photoinitiator are in a weight ratio of (10-12):(8-10):(1-2). The photoinitiator includes at least one of 2,2-dimethoxy-2-phenylacetophenone and 2-hydroxy-2-methyl-1-phenyl-1-propanone. The mercapto-containing alcohol compound includes at least one of 3-mercapto-1,2-propanediol and 3-mercapto-1-propanol.
[0123] In the embodiments of this application, the reaction temperature of the first reaction can be 20°C, 20.5°C, 21°C, 21.5°C, 22°C, 22.5°C, 23°C, 23.5°C, 24°C, 24.5°C, 25°C, 26°C, 27°C, 28°C, 29°C, 30°C, etc., preferably 25°C; the reaction time can be 2 hours, 2.5 hours, 3 hours, etc.
[0124] It should be noted that the reaction solvent for the first reaction is not particularly limited. A commonly used solvent in the field can be selected based on the solubility of the reactants and the reaction temperature. For example, organic solvents such as tetrahydrofuran can be used as the reaction solvent for the first reaction. Furthermore, the post-purification processing of the product after the first reaction is also not particularly limited. It generally includes preliminary separation steps such as extraction, filtration, and centrifugation; concentration and drying steps such as rotary evaporation, freeze-drying, and vacuum drying; and product purification steps such as recrystallization, column chromatography, distillation, activated carbon decolorization, and washing. Specifically, the post-purification processing of the product after the first reaction can be performed as follows: After the reaction, the reaction solution is quenched with water, extracted 1-3 times with ethyl acetate, and the organic phase is washed 1-3 times with water and saturated brine, respectively. After drying with anhydrous sodium sulfate, it is concentrated and recrystallized with n-hexane / ethyl acetate (5:1) to obtain intermediate A.
[0125] In the embodiments of this application, the operation of adding eugenol to the premixed system and heating it to 80-90°C in the second reaction described above can be specifically carried out as follows: Eugenol is slowly added to the premixed system (e.g., at a rate of 1-2 drops per second) while stirring and gradually heating (e.g., from room temperature at a heating rate of 3-5°C / min) to 80-90°C, for example, 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C, 90°C, etc. Meanwhile, the reaction temperature in the second reaction described above can be 110°C, 111°C, 112°C, 113°C, 114°C, 115°C, 116°C, 117°C, 118°C, 119°C, 120°C, etc., and the reaction time can be 3 hours, 3.5 hours, 4 hours, etc.
[0126] Furthermore, the reaction solvent for the second reaction is not particularly limited. A commonly used solvent in the field can be selected based on the solubility of the reactants and the reaction temperature. For example, organic solvents such as dimethyl sulfoxide can be used as the reaction solvent for the second reaction. In addition, the post-purification processing of the product after the second reaction is also not particularly limited. It generally includes preliminary separation steps such as extraction, filtration, and centrifugation; concentration and drying steps such as rotary evaporation, freeze-drying, and vacuum drying; and product purification steps such as recrystallization, column chromatography, distillation, activated carbon decolorization, and washing. Specifically, the post-purification processing of the product after the second reaction can be performed as follows: After the reaction is complete, cool to room temperature, slowly pour into ice water, stir for 30 minutes, filter to collect the solid, wash, and dry to obtain intermediate B.
[0127] In the embodiments of this application, the temperature of the third reaction can be 40°C, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C, 49°C, 50°C, etc., and the reaction time can be 3 hours, 3.5 hours, 4 hours, etc.
[0128] Furthermore, the reaction solvent for the third reaction is not particularly limited. A commonly used solvent in the field can be selected based on the solubility of the reactants and the reaction temperature. For example, anhydrous tetrahydrofuran or other organic solvents can be used as the reaction solvent for the third reaction. In addition, the post-treatment purification of the product after the third reaction is also not particularly limited. Generally, it includes preliminary separation steps such as extraction, filtration, and centrifugation; concentration and drying steps such as rotary evaporation, freeze-drying, and vacuum drying; and product purification steps such as recrystallization, column chromatography, distillation, activated carbon decolorization, and washing. Specifically, the post-purification processing of the product after the third reaction can be performed as follows: After the reaction, the reaction solution is neutralized with saturated sodium bicarbonate solution to make the pH of the reaction solution neutral; the neutralized mixture is transferred to a separatory funnel, ethyl acetate is added for extraction, the organic phase is extracted by separation, the organic phase is washed with water, washed with saturated brine and dried with anhydrous sodium sulfate and then concentrated, and finally purified by rapid column chromatography (the concentrated product is dissolved in a small amount of dichloromethane, slowly loaded onto the silica gel surface along the column wall with a dropper, the stopcock is opened at the bottom of the column, and rapid washing is performed with dichloromethane as the eluent, the eluent is collected and concentrated and dried) to obtain intermediate C.
[0129] In the embodiments of this application, the reaction temperature of the fourth reaction can be 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, 29°C, 30°C, etc., and the reaction time can be 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, etc.
[0130] Furthermore, the reaction solvent for the fourth reaction is not particularly limited. A commonly used solvent in the field can be selected based on the solubility of the reactants and the reaction temperature. For example, anhydrous tetrahydrofuran or other organic solvents can be used as the reaction solvent for the fourth reaction. Additionally, the post-purification processing of the product after the fourth reaction is also not particularly limited. It generally includes preliminary separation steps such as extraction, filtration, and centrifugation; concentration and drying steps such as rotary evaporation, freeze-drying, and vacuum drying; and product purification steps such as recrystallization, column chromatography, distillation, activated carbon decolorization, and washing. Specifically, the post-purification processing of the product after the fourth reaction can be performed as follows: the residue is dissolved in ethyl acetate, washed successively with cold water and saturated brine, dried over anhydrous sodium sulfate, concentrated, and purified by silica gel column chromatography (petroleum ether / ethyl acetate gradient elution), concentrated under reduced pressure, and dried under vacuum to obtain the target product – the compound shown in Formula II.
[0131] In the embodiments of this application, the weight ratio of the 4-hydroxybenzaldehyde, the phosphorylation reagent, and the alkaline catalyst is (10-12):(18-22):(13-15), for example, it can be 10:18:13, 10:18:15, 10:18:14, 11:18:13, 12:18:13, 10:19:13, 10:20:13, etc.;
[0132] And / or, the weight ratio of the paraformaldehyde, the ethylenediamine, and the eugenol is (10-12):(11-13):(30-35), for example, it can be 10:11:30, 10:11:31, 10:11:34, 10:11:35, 11:11:30, 12:11:30, 10:12:30, 10:13:35, etc.;
[0133] And / or, the weight ratio of intermediate A, intermediate B and acidic catalyst is (10-12):(12-15):(1-2), for example, it can be 10:12:1, 10:12:2, 11:12:1, 12:12:1, 10:13:1, 10:15:1, 10:15:2, etc.;
[0134] And / or, the weight ratio of the intermediate C, the thiol-containing alcohol compound, and the photoinitiator is (10-12):(8-10):(1-2), for example, 10:11:1, 12:11:2, 11:8:1, 11:10:2, etc.
[0135] A third aspect of this application provides a flame retardant. According to embodiments of this application, the flame retardant comprises a compound as described in any one of the first aspects or a compound prepared using the method described in any one of the second aspects.
[0136] The flame retardant described in the above embodiments of this application comprises the compound described in any one of the first aspects or a compound prepared by the method described in any one of the second aspects. Therefore, the flame retardant possesses multiple functional properties such as excellent flame retardancy, reactivity, and energy dissipation capacity.
[0137] A fourth aspect of this application discloses a toughening agent. According to embodiments of this application, the toughening agent comprises the compound described in any one of the first aspects or a compound prepared using the method described in any one of the second aspects.
[0138] The toughening agent described in the above embodiments of this application comprises the compound described in any one of the first aspects or a compound prepared by the method described in any one of the second aspects. Therefore, the toughening agent possesses multiple functional properties such as excellent flame retardancy, reactivity, and energy dissipation capability.
[0139] A fifth aspect of this application discloses a material modifier. According to embodiments of this application, the material modifier comprises a compound as described in any one of the first aspects or a compound prepared using the method described in any one of the second aspects.
[0140] The material modifier described in the above embodiments of this application comprises a compound as described in any one of the first aspects or a compound prepared using the method described in any one of the second aspects. Therefore, the material modifier possesses multiple functional properties such as excellent flame retardancy, reactivity, and energy dissipation capability.
[0141] A sixth aspect of this application discloses a polymer material. According to embodiments of this application, the raw materials for the polymer material include the compounds described in any one of the first aspects or compounds prepared using the preparation method of the compounds described in any one of the second aspects.
[0142] The polymer material described in the above embodiments of this application is modified by introducing the compound described in any one of the first aspects or by using the preparation method of the compound described in any one of the second aspects. As a result, the overall properties of the polymer material, such as flame retardant properties and mechanical properties, are significantly improved.
[0143] In some other embodiments of this application, the polymeric material comprises the following raw materials in parts by weight:
[0144] 70-80 parts of a polylactic acid compound containing a carboxyl group and 3-4 parts of the compound.
[0145] In the embodiments of this application, the above-mentioned carboxyl-containing polylactic acid compounds (or carboxylated polylactic acid) are a class of polylactic acid (structural formula H-[OCHCH3CO)). n Biodegradable polymers are formed by introducing carboxyl (-COOH) functional groups into their molecular chains through chemical modification, using -OH (n being the number of repeating units) as the backbone. Specifically, commercially available products such as carboxylated PLA, carboxylated PEG-PLA copolymer, and carboxylated PPG-PLA copolymer, produced by Meiluo Technology Co., Ltd., can be used, with weight parts of 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, and 80 parts, etc.
[0146] In some other embodiments of this application, the polymer material further includes the following raw materials in parts by weight:
[0147] 20-22 parts of cellulose compounds;
[0148] And / or, by weight, the polymeric material further includes the following raw materials:
[0149] 20-22 parts of cellulose compounds, 8-10 parts of plasticizer, 1-2 parts of lubricant, and 0.1-0.2 parts of esterification catalyst;
[0150] And / or, by weight, the polymeric material further includes the following raw materials:
[0151] The mixture contains 20-22 parts of cellulose compounds, 8-10 parts of plasticizer, 1-2 parts of lubricant, 0.1-0.2 parts of esterification catalyst, and 3-4 parts of filler.
[0152] In the embodiments of this application, the above-mentioned cellulose compounds are compounds with cellulose as the backbone, which retain or introduce hydroxyl (-OH) or carboxyl (-COOH) functional groups in their molecular chains through chemical modification or physical modification, and their weight parts can be 20 parts, 20.5 parts, 21 parts, 21.5 parts, 22 parts, etc.
[0153] In the embodiments of this application, the weight parts of the plasticizer may be 8.0 parts, 8.1 parts, 8.2 parts, 8.3 parts, 8.4 parts, 8.5 parts, 8.6 parts, 8.7 parts, 8.8 parts, 8.9 parts, 9.0 parts, 9.1 parts, 9.2 parts, 9.3 parts, 9.4 parts, 9.5 parts, 9.6 parts, 9.7 parts, 9.8 parts, 9.9 parts, 10.0 parts, etc.; the weight parts of the lubricant may be 1.0 part. The weight percentages of the above esterification reaction catalyst can be 0.1 parts, 0.2 parts, etc.; the weight percentages of the above filler can be 3.0 parts, 3.1 parts, 3.2 parts, 3.3 parts, 3.4 parts, 3.5 parts, 3.6 parts, 3.7 parts, 3.8 parts, 3.9 parts, 4.0 parts, etc.
[0154] In some other embodiments of this application, the cellulose compound includes at least one of cellulose acetate, carboxymethyl cellulose, and hydroxyethyl cellulose;
[0155] And / or, the plasticizer includes at least one of polyethylene glycol, triacetin, and citrate;
[0156] And / or, the lubricant comprises at least one of zinc stearate, calcium stearate, barium stearate, or polyethylene wax;
[0157] And / or, the filler comprises at least one of layered silicate and nano-silica;
[0158] And / or, the esterification catalyst includes at least one of zinc acetate and zinc propionate.
[0159] And / or, the cellulose compound includes at least one of cellulose acetate, carboxymethyl cellulose and hydroxyethyl cellulose, preferably cellulose acetate;
[0160] And / or, the plasticizer includes at least one of polyethylene glycol, triacetin, and citrate, preferably polyethylene glycol;
[0161] And / or, the lubricant comprises at least one of zinc stearate, calcium stearate, barium stearate and polyethylene wax, preferably zinc stearate;
[0162] And / or, the filler comprises at least one of layered silicates such as montmorillonite and nano-silica, preferably montmorillonite;
[0163] And / or, the esterification catalyst includes at least one of zinc acetate and zinc propionate, preferably zinc acetate.
[0164] In some other embodiments of this application, the biodegradability of the polymer material is 82.7-88.9%.
[0165] In the embodiments of this application, the biodegradability of the above-mentioned polymeric material can be tested according to test standards such as GB / T19811-2005. The biodegradability of the obtained material is maintained at 82.7-88.9%, indicating that its biodegradability performance is excellent.
[0166] In some other embodiments of this application, the tensile strength of the polymer material is 54.2 to 60.5 MPa.
[0167] In the embodiments of this application, the tensile strength of the above-mentioned polymer material can be tested according to test standards such as GB / T1040.2-2006. The tensile strength of the obtained material is maintained at 54.2 to 60.5 MPa, indicating that its tensile strength performance is excellent.
[0168] In some other embodiments of this application, the limiting oxygen index of the polymeric material is 30.2 to 33.4%.
[0169] In the embodiments of this application, the limiting oxygen index of the above-mentioned polymer material can be tested according to test standards such as GB / T2406.2-2009 and GB / T2406-2008. The limiting oxygen index of the obtained material is maintained at 30.2 to 33.4%, indicating that it has excellent flame retardant properties.
[0170] A seventh aspect of this application provides a method for preparing a polymeric material as described in any one of the sixth aspects above. According to an embodiment of this application, the method for preparing the polymeric material includes the following steps:
[0171] The raw material components of a polymer material are mixed to obtain a mixture;
[0172] The mixture is melt-blended and extruded to obtain the polymer material.
[0173] The present application describes a method for preparing polymeric materials according to the above embodiments. This method introduces the aforementioned compounds through melt blending and extrusion molding to modify the material. Consequently, the overall properties of the polymeric material, including its flame retardant and mechanical properties, are significantly improved.
[0174] In some other embodiments of this application, the equipment for melt blending and extrusion molding of the mixture includes a twin-screw extruder. The operating parameters of the twin-screw extruder include: conveying section temperature of 150-160°C, melting section temperature of 170-180°C, mixing section temperature of 180-190°C, homogenization section temperature of 175-185°C, and die head temperature of 170-180°C.
[0175] An eighth aspect of this application discloses a packaging article. According to an embodiment of this application, the raw materials of the packaging article include the compound described in any one of the first aspects, the compound prepared by the method described in any one of the second aspects, the polymer material described in any one of the sixth aspects, or the polymer material prepared by the method described in any one of the seventh aspects.
[0176] The packaging articles described in the above embodiments of this application are made from the aforementioned compounds or polymeric materials. Therefore, these packaging articles possess excellent flame-retardant properties and mechanical properties.
[0177] In some other embodiments of this application, the packaging articles include at least one of coffee cup lids, milk tea cups, packaging bags, lunch boxes, and headphone cases. Specifically, they may be food packaging articles such as coffee cup lids, milk tea cups, packaging bags, and lunch boxes, or electronic product packaging articles such as mobile phone cases and headphone cases.
[0178] The embodiments of this application are described in detail below. It should be noted that the embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. In addition, unless otherwise specified, all reagents used in the following embodiments are commercially available or can be synthesized according to the methods described herein or known methods. For reaction conditions not listed, they are also readily available to those skilled in the art.
[0179] Example 1
[0180] This embodiment provides a compound, the chemical structural formula of which is shown in Formula II;
[0181] Formula II:
[0182] This embodiment also provides a method for preparing the compound shown in Formula II above, including the following steps:
[0183] S1: Under a nitrogen protective atmosphere, 10 parts by weight of 4-hydroxybenzaldehyde were dissolved in 150 parts by weight of tetrahydrofuran, cooled to 0°C in an ice bath, and then 13 parts by weight of triethylamine (as a basic catalyst) were added and stirred for 30 min. Subsequently, 18 parts by weight of phosphorus oxychloride (as a phosphorylation reagent) were slowly added dropwise. After the addition was completed, the temperature was raised to 25°C and the reaction was continued for 2 h. After the reaction was completed, the reaction solution was poured into ice water, adjusted to pH=7 with saturated sodium bicarbonate, extracted three times with ethyl acetate, the organic phases were combined and washed three times with water and saturated brine respectively, dried with anhydrous sodium sulfate, concentrated and recrystallized with n-hexane / ethyl acetate (5:1) to obtain intermediate A;
[0184] S2: Mix 10 parts by weight of paraformaldehyde with 60 parts by weight of dimethyl sulfoxide, heat to 50°C and stir for 15 min, cool to 25°C, add 11 parts by weight of ethylenediamine, stir for 10 min, then slowly add 30 parts by weight of eugenol while stirring, and gradually increase the temperature from room temperature to 80°C at a rate of 3°C / min. After the addition is complete, raise the temperature to 110°C and react for 3 h. After the reaction is complete, cool to room temperature, slowly pour into ice water, stir for 30 min, filter to collect the solid, wash, and dry to obtain intermediate B;
[0185] S3: Mix 10 parts by weight of intermediate A, 12 parts by weight of intermediate B, and 100 parts by weight of anhydrous tetrahydrofuran, stir well, then add 1 part by weight of acetic acid (as an acidic catalyst), raise the temperature to 50°C, and react for 3 hours. After the reaction is complete, neutralize the acid with saturated sodium bicarbonate solution, extract the organic phase by liquid-liquid extraction, wash the organic phase three times with water and three times with saturated brine, dry it with anhydrous sodium sulfate, concentrate it, and finally purify it by rapid column chromatography (dissolve the concentrated product in a small amount of dichloromethane, slowly load it onto the silica gel surface along the column wall with a dropper, open the stopcock at the bottom of the column, use dichloromethane as the eluent for rapid washing, collect the eluent and concentrate and dry it) to obtain intermediate C;
[0186] S4: Under a nitrogen protective atmosphere, 10 parts by weight of intermediate C, 8 parts by weight of 3-mercapto-1,2-propanediol, 1 part by weight of 2,2-dimethoxy-2-phenylacetophenone, and 100 parts by weight of anhydrous tetrahydrofuran are mixed and irradiated with ultraviolet light (light intensity of 15 mW / cm²). 2Under a light irradiation distance of 10 cm, the mixture was stirred for 2 h. The solvent was removed by vacuum distillation, and the residue was dissolved in ethyl acetate. The residue was washed successively with cold water and saturated brine, dried over anhydrous sodium sulfate, concentrated, and purified by silica gel column chromatography (petroleum ether / ethyl acetate gradient elution, concentrated under reduced pressure, and dried under vacuum) to obtain the target product – the compound shown in Formula II.
[0187] The product yield of the compound shown in Formula II obtained in this embodiment was 65.5%.
[0188] Example 2
[0189] This embodiment provides a compound represented by Formula II and a method for its preparation, with the preparation method adjusted as follows:
[0190] S1: Under a nitrogen protective atmosphere, 12 parts by weight of 4-hydroxybenzaldehyde were dissolved in 200 parts by weight of tetrahydrofuran, cooled to 0°C in an ice bath, and then 15 parts by weight of triethylamine were added and stirred for 40 min. Subsequently, 22 parts by weight of phosphorus oxychloride were slowly added dropwise. After the addition was completed, the temperature was raised to 25°C and the reaction was continued for 3 h. After the reaction was completed, post-treatment was performed (the specific post-treatment process was the same as in Example 1) to obtain intermediate A.
[0191] S2: Mix 12 parts by weight of paraformaldehyde with 60 parts by weight of dimethyl sulfoxide, heat to 50°C and stir for 15 min, cool to 25°C, add 13 parts by weight of ethylenediamine, stir for 10 min, then slowly add 35 parts by weight of eugenol while stirring, and gradually increase the temperature from room temperature to 90°C at a rate of 3°C / min. After the addition is complete, raise the temperature to 120°C and react for 4 h. After the reaction is complete, cool to room temperature, dilute with chloroform, slowly pour into ice water, stir for 30 min, filter to collect the solid, wash, and dry to obtain intermediate B;
[0192] S3: Mix 12 parts by weight of intermediate A, 15 parts by weight of intermediate B, and 150 parts by weight of anhydrous tetrahydrofuran, stir well, then add 2 parts by weight of acetic acid, raise the temperature to 50°C, and react for 4 hours. After the reaction is complete, neutralize the acid with saturated sodium bicarbonate solution, extract the organic phase by liquid-liquid extraction, wash the organic phase three times with water and three times with saturated brine, dry it with anhydrous sodium sulfate, and concentrate it. Purify the concentrated product (the specific purification process is the same as in Example 1) to obtain intermediate C.
[0193] S4: Under a nitrogen protective atmosphere, 12 parts by weight of intermediate C, 10 parts by weight of 3-mercapto-1,2-propanediol, 2 parts by weight of 2,2-dimethoxy-2-phenylacetophenone, and 150 parts by weight of anhydrous tetrahydrofuran were mixed and reacted with stirring for 4 hours under ultraviolet light (the light intensity and light distance were the same as in Example 1). The solvent was removed by vacuum distillation, and the product was post-treated (the specific post-treatment process was the same as in Example 1) to obtain the target product - the compound shown in Formula II.
[0194] The product yield of the compound shown in Formula II obtained in this embodiment was 65.6%.
[0195] Example 3
[0196] This embodiment provides a compound represented by Formula II and a method for its preparation, with the preparation method adjusted as follows:
[0197] S1: Under a nitrogen protective atmosphere, 11 parts by weight of 4-hydroxybenzaldehyde were dissolved in 175 parts by weight of tetrahydrofuran, cooled to 0°C in an ice bath, and then 14 parts by weight of triethylamine were added. The mixture was stirred for 35 minutes, and then 20 parts by weight of phosphorus oxychloride were slowly added dropwise. After the addition was complete, the temperature was raised to 25°C and the reaction continued for 2.5 hours. After the reaction was completed, the mixture was post-treated (the specific post-treatment process was the same as in Example 1) to obtain intermediate A.
[0198] S2: Mix 11 parts by weight of paraformaldehyde with 60 parts by weight of dimethyl sulfoxide, heat to 50°C and stir for 15 min, cool to 25°C, add 12 parts by weight of ethylenediamine, stir for 10 min, stir evenly at room temperature, then slowly add 32.5 parts by weight of eugenol while stirring, and gradually increase the temperature from room temperature to 85°C at a rate of 3°C / min. After the addition is complete, raise the temperature to 115°C and react for 3.5 h. After the reaction is complete, cool to room temperature and perform post-processing (the specific post-processing process is the same as in Example 1) to obtain intermediate B.
[0199] S3: Mix 11 parts by weight of intermediate A, 13.5 parts by weight of intermediate B, and 125 parts by weight of tetrahydrofuran, stir well, then add 1.5 parts by weight of acetic acid, raise the temperature to 45°C, and react for 3.5 hours. After the reaction is complete, neutralize the acid with saturated sodium bicarbonate solution, extract the organic phase by liquid-liquid extraction, wash the organic phase three times with water and three times with saturated brine, dry it with anhydrous sodium sulfate, and concentrate it. Purify the concentrated product (the specific purification process is the same as in Example 1) to obtain intermediate C.
[0200] S4: Under a nitrogen protective atmosphere, 11 parts by weight of intermediate C, 9 parts by weight of 3-mercapto-1,2-propanediol, 1.5 parts by weight of 2,2-dimethoxy-2-phenylacetophenone, and 125 parts by weight of anhydrous tetrahydrofuran were mixed and reacted with stirring for 4 hours under ultraviolet light (the light intensity and light distance were the same as in Example 1). The solvent was removed by vacuum distillation, and the product was post-treated (the specific post-treatment process was the same as in Example 1) to obtain the target product - the compound shown in Formula II.
[0201] The product yield of the compound shown in Formula II obtained in this embodiment was 68.6%.
[0202] Example 4
[0203] This embodiment provides a compound and its preparation method, which differs from Example 1 only in that:
[0204] (1) Step S4: Adjust 3-mercapto-1,2-propanediol to 3-mercapto-1-propanol.
[0205] Example 5
[0206] This embodiment provides a biodegradable polymer material, which, by weight, comprises the following raw materials:
[0207] 70 parts of a carboxyl-containing polylactic acid compound (purchased from Meiluo Technology Co., Ltd., product name: carboxylated PLA), 20 parts of cellulose acetate (CAS No. 9004-35-7), 8 parts of a plasticizer (specifically polyethylene glycol 1000), 1 part of a lubricant (specifically stearic acid, CAS No. 57-11-4), 3 parts of the compound of formula II obtained in Example 1, 3 parts of montmorillonite, and 0.1 parts of zinc acetate.
[0208] The preparation method of the above-mentioned polymer material in this embodiment includes the following steps:
[0209] The raw materials contained in the polymer composite material are added into a high-speed mixer and stirred evenly to obtain a mixed raw material;
[0210] The mixed raw materials are added to a twin-screw extruder for melt blending, extrusion, cooling, and pelletizing to obtain polymer materials. The operating parameters of the twin-screw extruder include: conveying section temperature of 155℃, melting section temperature of 175℃, mixing section temperature of 185℃, homogenization section temperature of 180℃, and die head temperature of 175℃.
[0211] Example 6
[0212] This embodiment provides a biodegradable polymer material, which, by weight, comprises the following raw materials:
[0213] 80 parts of a carboxyl-containing polylactic acid compound (purchased from Meiluo Technology Co., Ltd., product name: carboxylated PEG-PLA copolymer), 22 parts of cellulose acetate (CAS No. 9004-35-7), 10 parts of plasticizer (specifically polyethylene glycol 1000), 2 parts of lubricant (specifically stearic acid, CAS No. 57-11-4), 4 parts of the compound of formula II obtained in Example 1, 4 parts of montmorillonite, and 0.2 parts of zinc acetate.
[0214] The preparation method of the polymer material described above in this embodiment is the same as that in Example 5.
[0215] Example 7
[0216] This embodiment provides a biodegradable polymer material, which, by weight, comprises the following raw materials:
[0217] 75 parts of a carboxyl-containing polylactic acid compound (purchased from Meiluo Technology Co., Ltd., product name: carboxylated PPG-PLA copolymer), 21 parts of cellulose acetate (CAS No. 9004-35-7), 9 parts of plasticizer (specifically polyethylene glycol 1000), 1.5 parts of lubricant (specifically stearic acid, CAS No. 57-11-4), 3.5 parts of the compound of formula II obtained in Example 1, 3.5 parts of montmorillonite, and 0.15 parts of zinc acetate.
[0218] The preparation method of the polymer material described above in this embodiment is the same as that in Example 5.
[0219] Example 8
[0220] This embodiment provides a biodegradable polymer material, which, by weight, comprises the following raw materials:
[0221] 75 parts of a carboxyl-containing polylactic acid compound (same as in Example 7) and 3.5 parts of the compound of formula II obtained in Example 1.
[0222] The preparation method of the polymer material described above in this embodiment is the same as that in Example 5.
[0223] Example 9
[0224] This embodiment provides a biodegradable polymer material, which, by weight, comprises the following raw materials:
[0225] 75 parts of a carboxyl-containing polylactic acid compound (same as in Example 7), 21 parts of cellulose acetate (CAS No. 9004-35-7), and 3.5 parts of the compound of formula II obtained in Example 1.
[0226] The preparation method of the polymer material described above in this embodiment is the same as that in Example 5.
[0227] Example 10
[0228] This embodiment provides a biodegradable polymer material, which, by weight, comprises the following raw materials:
[0229] 75 parts of a carboxyl-containing polylactic acid compound (same as in Example 7), 21 parts of cellulose acetate (CAS No. 9004-35-7), 9 parts of a plasticizer (specifically polyethylene glycol 1000), 1.5 parts of a lubricant (specifically stearic acid, CAS No. 57-11-4), 3.5 parts of the compound of formula II obtained in Example 1, and 0.15 parts of zinc acetate.
[0230] The preparation method of the polymer material described above in this embodiment is the same as that in Example 5.
[0231] Example 11
[0232] This embodiment provides a biodegradable polymer material and its preparation method, which differs from Example 6 only in that:
[0233] (1) Cellulose compounds were adjusted to hydroxyethyl cellulose;
[0234] (2) The plasticizer was changed to hydroxyethyl cellulose;
[0235] (3) The lubricant was changed to calcium stearate;
[0236] (4) The catalyst for the esterification reaction was changed to zinc propionate;
[0237] (5) The filler was adjusted to nano-silica.
[0238] Example 12
[0239] This embodiment provides a biodegradable polymer material and its preparation method, which differs from Example 6 only in that:
[0240] (1) The compound of formula II obtained in Example 1 was modified to the compound obtained in Example 4.
[0241] Comparative Example 1
[0242] This comparative example provides a polymer composite material and its preparation method, which differs from Example 7 only in that:
[0243] (1) The weight of the compound shown in Formula II is adjusted to 0 parts (i.e., no compound shown in Formula I is added).
[0244] Comparative Example 2
[0245] This comparative example provides a polymer composite material and its preparation method, which differs from Example 7 only in that:
[0246] (1) The compound shown in Formula II was modified to a commercially available flame retardant (purchased from Zhangjiagang Chuangli New Materials Co., Ltd., the product is a phosphate ester flame retardant).
[0247] Test case
[0248] This test example demonstrates the performance testing of the polymer composite materials obtained in Examples 5-12 and Comparative Examples 1-2.
[0249] The testing standards and methods are as follows:
[0250] (1) The biodegradation rate of the examples and comparative examples was determined according to the national standard GB / T19811-2005;
[0251] (2) The tensile properties of the examples and comparative examples were determined according to the national standard GB / T1040.2-2006;
[0252] (3) The limiting oxygen index of the examples and comparative examples was determined using the national standard GB / T2406-2008.
[0253] The test results are shown in Table 1.
[0254] Table 1
[0255] Test sample Biodegradation rate (%) Tensile strength (MPa) Limiting oxygen index (%) Example 5 85.2 58.3 31.5 Example 6 82.7 59.1 32.8 Example 7 86.0 60.5 33.4 Example 8 88.9 54.2 30.6 Example 9 87.1 56.8 30.2 Example 10 84.5 58.0 31.0 Example 11 83.8 57.2 30.5 Example 12 84.0 57.9 31.8 Comparative Example 1 93.0 48.5 19.0 Comparative Example 2 75.3 50.1 26.5
[0256] As shown in Table 1, the sample with the compound shown in Formula I exhibited excellent biodegradability, outstanding tensile strength, and a high limiting oxygen index, significantly superior to Comparative Example 1 without the modifier and Comparative Example 2 using a commercially available flame retardant. This indicates that the compound provided in this application, when used to modify materials such as polylactic acid, can significantly improve the flame retardant and mechanical properties of the materials, and has a wide range of applications.
[0257] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.
[0258] Although embodiments of this application have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting this application. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of this application.
Claims
1. A compound, characterized in that, The general chemical structural formula of the compound is shown in Formula I; Equation I: R is a substituent containing a hydroxyl group.
2. The compound according to claim 1, characterized in that, R is selected from any of the following substituents:
3. The compound according to claim 1, characterized in that, The chemical structural formula of the compound is shown in Formula II; Formula II:
4. A method for preparing a compound according to any one of claims 1 to 3, characterized in that, The method for preparing the compound includes the following steps: 4-hydroxybenzaldehyde and a phosphorylating agent were reacted in the first reaction to give intermediate A; A second reaction is carried out with paraformaldehyde, ethylenediamine and eugenol to obtain intermediate B; Intermediate A and intermediate B are subjected to a third reaction to obtain intermediate C; The intermediate C and a thiol-containing alcohol compound are subjected to a fourth reaction to obtain the compound; The chemical structural formula of intermediate A is shown below: The chemical structural formula of intermediate B is shown below: The chemical structural formula of intermediate C is shown below:
5. The method for preparing the compound according to claim 4, characterized in that, The step of reacting 4-hydroxybenzaldehyde with a phosphorylating agent to obtain intermediate A includes the following process: Under the protection of an inert atmosphere and the action of an alkaline catalyst, the 4-hydroxybenzaldehyde and the phosphorylating agent are subjected to the first reaction at a temperature of 20-30°C for 2-3 hours to obtain the intermediate A; The weight ratio of the 4-hydroxybenzaldehyde, the phosphorylating agent, and the alkaline catalyst is (10-12):(18-22):(13-15), the alkaline catalyst includes at least one of triethylamine, pyridine, and diisopropylethylamine, and the phosphorylating agent includes at least one of phosphorus oxychloride and phosphorus oxybromide. And / or, the step of subjecting paraformaldehyde, ethylenediamine, and eugenol to a second reaction to obtain intermediate B includes the following processes: The paraformaldehyde and the ethylenediamine are mixed to obtain a premixed system; Add the eugenol dropwise to the premixed system and heat to 80-90°C. After the addition is complete, heat to 110-120°C to carry out the second reaction for 3-4 hours to obtain intermediate B. The weight ratio of the paraformaldehyde, the ethylenediamine and the eugenol is (10-12):(11-13):(30-35); And / or, the step of subjecting intermediate A and intermediate B to a third reaction to obtain intermediate C includes the following process: Under the action of an acidic catalyst, intermediate A and intermediate B are subjected to the third reaction at a temperature of 40-50°C for 3-4 hours to obtain intermediate C; The weight ratio of intermediate A, intermediate B and acidic catalyst is (10-12):(12-15):(1-2), and the acidic catalyst includes at least one of acetic acid and p-toluenesulfonic acid. And / or, the step of subjecting the intermediate C and a thiol-containing alcohol compound to a fourth reaction to obtain the compound includes the following process: Under light irradiation and with the aid of a photoinitiator, the intermediate C and the thiol-containing alcohol compound were subjected to the fourth reaction at a temperature of 20–30°C for 2–4 hours to obtain the compound. The intermediate C, the mercapto-containing alcohol compound, and the photoinitiator are in a weight ratio of (10-12):(8-10):(1-2). The photoinitiator includes at least one of 2,2-dimethoxy-2-phenylacetophenone and 2-hydroxy-2-methyl-1-phenyl-1-propanone. The mercapto-containing alcohol compound includes at least one of 3-mercapto-1,2-propanediol and 3-mercapto-1-propanol.
6. A flame retardant, characterized in that, The flame retardant includes the compound according to any one of claims 1 to 3 or the compound prepared by the method of any one of claims 4 to 5.
7. A toughening agent, characterized in that, The toughening agent includes the compound according to any one of claims 1 to 3 or the compound prepared by the method of any one of claims 4 to 5.
8. A material modifier, characterized in that, The material modifier includes the compound according to any one of claims 1 to 3 or the compound prepared by the method of any one of claims 4 to 5.
9. A polymer material, characterized in that, The raw materials for the polymer material include the compounds according to any one of claims 1 to 3 or the compounds prepared by the method of any one of claims 4 to 5.
10. The polymer material according to claim 9, characterized in that, The polymer material comprises the following raw materials in parts by weight: 70-80 parts of a polylactic acid compound containing a carboxyl group and 3-4 parts of the compound.
11. The polymer material according to claim 10, characterized in that, The polymer material further includes the following raw materials in parts by weight: 20-22 parts of cellulose compounds; And / or, by weight, the polymeric material further includes the following raw materials: 20-22 parts of cellulose compounds, 8-10 parts of plasticizer, 1-2 parts of lubricant, and 0.1-0.2 parts of esterification catalyst; And / or, by weight, the polymeric material further includes the following raw materials: The mixture contains 20-22 parts of cellulose compounds, 8-10 parts of plasticizer, 1-2 parts of lubricant, 0.1-0.2 parts of esterification catalyst, and 3-4 parts of filler.
12. The polymer material according to claim 11, characterized in that, The cellulose compounds include at least one of cellulose acetate, carboxymethyl cellulose and hydroxyethyl cellulose; And / or, the plasticizer includes at least one of polyethylene glycol, triacetin, and citrate; And / or, the lubricant comprises at least one of zinc stearate, calcium stearate, barium stearate, and polyethylene wax; And / or, the filler comprises at least one of layered silicate and nano silica; And / or, the esterification catalyst includes at least one of zinc acetate and zinc propionate.
13. The polymer material according to any one of claims 9 to 12, characterized in that, The biodegradability of the polymer material is 82.7%–88.9%.
14. The polymer material according to any one of claims 9 to 12, characterized in that, The tensile strength of the polymer material is 54.2–60.5 MPa.
15. The polymer material according to any one of claims 9 to 12, characterized in that, The limiting oxygen index of the polymer material is 30.2 to 33.4%.
16. A method for preparing a polymer material according to any one of claims 9 to 15, characterized in that, The preparation method of the polymer material includes the following steps: The raw material components of a polymer material are mixed to obtain a mixture; The mixture is melt-blended and extruded to obtain the polymer material.
17. The method for preparing the polymer material according to claim 16, characterized in that, The equipment for melt blending and extrusion molding of the mixture includes a twin-screw extruder. The operating parameters of the twin-screw extruder include: conveying section temperature of 150-160°C, melting section temperature of 170-180°C, mixing section temperature of 180-190°C, homogenization section temperature of 175-185°C, and die head temperature of 170-180°C.
18. A type of packaging product, characterized in that, The raw materials for the packaging products include the compounds according to any one of claims 1 to 3, the compounds prepared by the method of the compounds according to any one of claims 4 to 5, the polymeric materials according to any one of claims 9 to 15, or the polymeric materials prepared by the method of the polymeric materials according to any one of claims 16 to 17.
19. The packaging article according to claim 18, characterized in that, The packaging products include at least one of coffee cup lids, milk tea cups, packaging bags, lunch boxes, and headphone cases.